ASSESSMENT OF THE RICE FIELD SUSTAINABILITY IN JAVA ON BASIS OF REGIONAL SPATIAL USE PLANNING (RTRW) - Nurwadjedi, Nurwadjedi; Mulyanto, Budi; Poniman, Aris (Badan Informasi Geospasial in Partnership with MAPIN, 2010)
The problems of the rice field sustainability in Java as the national rice producer are induced by the rice field land conversion into settlement and industrial areas due to the increase of population. The rice field conversion causes the decrease of both land quantity and quality. As mentioned in Act Number 26/2007 concerning Spatial Use management, the goal of implementing the spatial use management is to achieve the protection of spatial use function and the prevention of the negative impacts of the environment resulted from the spatial use implementation. The objective of this study is to assess the consistency of the governmental policies in implementing the Act Number 26/2007 to achieve the rice field sustainability on the basis of agro-ecological concept. By using the GIS modelbase, the rice field agro-ecological zones proposed as standard rice field areas for the benchmark of the sustainable rice field agriculture management system were synthesized from the spatial database of land system, land cover, area status, agro-climate, irrigation condition, social and culture integrated in the administration boundary layers. The results show that the governmental policies from non-agricultural sector in allocating the area status of the settlement areas as presented at the provincial regional spatial use planning map (RTRW map) have not fully consistent to the regulations as stated in Act Number 26/2007 for protecting the productive rice field function as the national rice producer. The potential loss of the rice production caused by the implementation of the rice field conversion into settlement areas allocated at the productive rice field agro-ecological zones is predicted 3.5 million tons per year.Key words: rice field agro-ecological zone, spatial use management, GIS modelbase, land conversion.ABSTRAKMasalah keberlanjutan lahan sawah di Jawa sebagai lumbung beras nasional dipicu oleh konversi lahan sawah menjadi daerah permukiman dan industri karena peningkatan jumlah penduduk. Konversi lahan sawah mengakibatkan penyusutan dan degradasi lahan sawah. Sebagaimana yang diamanatkan dalam Undang-Undang No.26/2007 tentang Penataan Ruang, tujuan penataan ruang adalah untuk melindungi fungsi penggunaan ruang dan mencegah dampak lingkungan sebagai akibat dari implementasi penggunaan ruang. Tujuan penelitian ini adalah untuk mengkaji konsistensi kebijakan pemerintah sebagai implementasi Undang-Undang No. 26/2007 dalam menjaga keberlanjutan lahan sawah berdasarkan konsep agrokologi. Dengan menggunakan basismodel SIG, zona agroekologi yang diusulkan sebagai acuan untuk penetapan luasan baku lahan sawah disintesa dari basisdata sistem lahan, penutup lahan, status kawasan, agroklimat, kondisi irigasi, dan sosial-budaya yang diintegrasikan dalam layer batas wilayah administrasi. Hasil penelitian menunjukkan bahwa kebijakan pemerintah di sektor non-pertanian dalam pengalokasian status kawasan permukiman ternyata tidak secara penuh konsisten dengan Undang-Undang No.26/2007 dalam menjaga keberlanjutan lahan sawah produkif sebagai lumbung beras nasional. Potensi kerugian proudksi beras dari akibat implementasi kebijakan tersebut diperkirakan mencapai 3,5 juta ton per tahun.Kata Kunci: zona agroekologi lahan sawah, penataan ruang, basismodel SIG, konversi lahan.